Impact of Smartphone Used on English Reading and Writing Skills Among Tertiary-Level EFL Learners - Marpaung, Marlin Steffi; Katemba, Caroline V.; Simanjuntak, Samuel M. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
In English education and teaching, technology has advanced at a rapid pace. Reading and writing are key learning abilities since reading allows students to have a broad understanding of the material and writing is a technique of expressing ideas, points of view, actions, and past experiences in written form, such as letters and notes. The purpose of this study is to discover the positive relationship between smartphone usage and students' English reading achievement, and the positive relationship between smartphone usage and students' English writing achievement among tertiary EFL students at Universitas Advent Indonesia. This study utilized a quantitative method with a descriptive correlation approach and the ballot system used in selecting the respondents. The population in this study were Universitas Advent Indonesia students who enrolled in the second semester of the 2019/2020 academic year with total respondents were 55 students, 26 were from General English 2 (Reading) and 29 were from General English 4 (Writing) subjects. The instrument used in this study was a questionnaire with reading and writing tests. The Pearson Product Moment Correlations was used. The findings showed that there is a strong positive relationship between smartphone usage and students' English reading achievement and a very strong positive relationship between smartphone usage and students' English writing achievement.